Nisekoi : false love. Vol. 15, Beauty contest - Komi, Naoshi, 1986- (Viz Media,LLC, 2016)
"It's hate at first sight when Raku Ichijo first meets Chitoge Kirisaki. But much to their chagrin, the two are forced into a false love relationship to keep the peace between their feuding gangster families. But what happens when Raku's childhood friend Yui declares her love for Raku, and he ends up spending the day with her after everyone in the house leaves for vacation?! When Chitoge and the others catch wind of it, they'll do anything to stop the two from being alone" -- page 4 of cover.